Air‐core fiber or photonic‐crystal rod, which is more suitable for energetic femtosecond pulse generation and three‐photon microscopy at the 1700‐nm window?. Issue 10 (13th June 2019) - Gan, Mengyao; He, Chen; Liu, Hongji; Zhuang, Ziwei; Qiu, Ping; Wang, Ke
Abstract: Energetic femtosecond pulses at the 1700‐nm window are a prerequisite for deep‐tissue three‐photon microscopy (3PM). Soliton self‐frequency shift (SSFS) in photonic‐crystal (PC) rod has been the only technique to generate such pulses suitable for 3PM. Here we demonstrate through SSFS in an air‐core fiber, we can generate most energetic femtosecond soliton pulses at the 1700‐nm window, 5.2 times higher than that from PC rod. However, the air‐core soliton pulse width is 5.9 times longer than that of PC rod soliton. Based on comparative 3PM excited with both air‐core and PC rod solitons, we propose the more suitable source for 3PM. We further elucidate the challenge of generating shorter soliton pulses from air‐core fibers through numerical simulation. Abstract : This study is the first demonstration of soliton self‐frequency shift in an air‐core fiber at the 1700‐nm window. The generated solitons are the most energetic among various optical waveguides. However, comparative 3PM experiments excited with both air‐core fiber solitons and PC rod solitons shows: PC rod solitons are still favored for 3PM in terms of signal level, due to the combined high pulse energy and short pulse width.